Implementasi Model Problem Based Learning Kaitannya dengan Critical Thinking Pembelajaran PAI Kelas IX di SMP N 1 Bantarsari Kabupaten Cilacap - Amalia Putri Soleha; Intan Nur Azizah (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This study discusses the implementation of the Problem Based Learning (PBL) model to improve critical thinking in Islamic Religious Education (PAI) learning at SMP Negeri 1 Bantarsari. The focus of this research is on the planning and implementation of the PBL model to improve students' critical thinking skills. The purpose of this study is to find out and describe in depth how the implementation of the Problem Based Learning model can contribute to improving students' critical thinking skills in the context of PAI learning. This type of research is a field research with a qualitative approach and is presented descriptively. The data collection techniques used include observation, interviews, and documentation, while data analysis is carried out through three stages, namely data reduction, data presentation, and drawing conclusions or verification. This research was conducted directly in the school environment so as to produce actual and contextual empirical data. The results of the study show that teachers have designed learning well through the preparation of teaching modules as guidelines. The implementation of learning is carried out in three main stages, namely planning, implementation, and evaluation. At the implementation stage, the PBL model is applied through five steps: (1) orientation to the problem, (2) organizing students to learn, (3) individual and group investigations, (4) presentation of discussion results, and (5) reflection on learning outcomes. Evaluation is carried out on an ongoing basis both during the learning process and at the end of the activity. The application of this Problem Based Learning model has proven to be effective in increasing students' critical thinking. Students show improved ability to analyze, evaluate, and solve problems relevant to PAI material. In addition, students also become more active, independent, and used to expressing opinions in group discussions. Interaction between students increases positively, creating a collaborative and participatory learning environment. This indicates that the use of the PBL model can be the right strategy in developing students' critical thinking skills at the junior secondary education level.